2020
DOI: 10.1186/s40644-019-0283-8
|View full text |Cite
|
Sign up to set email alerts
|

A Delta-radiomics model for preoperative evaluation of Neoadjuvant chemotherapy response in high-grade osteosarcoma

Abstract: Background: The difficulty of assessment of neoadjuvant chemotherapeutic response preoperatively may hinder personalized-medicine strategies that depend on the results from pathological examination. Methods: A total of 191 patients with high-grade osteosarcoma (HOS) were enrolled retrospectively from November 2013 to November 2017 and received neoadjuvant chemotherapy (NCT). A cutoff time of November 2016 was used to divide the training set and validation set. All patients underwent diagnostic CTs before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 45 publications
(64 reference statements)
3
66
0
Order By: Relevance
“…We proposed Delta-radiomics signature and compared it with single-time-point radiomics signature at TP1. Interestingly, Delta-radiomics signature of LL approach showed higher AUC, which agrees with a recent paper ( 26 ). Although we did not find significant difference of AUC between them, the lower 95% confidence interval of AUC at TP1 is 0.51 in the test set, indicating an insufficient diagnosis efficiency.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We proposed Delta-radiomics signature and compared it with single-time-point radiomics signature at TP1. Interestingly, Delta-radiomics signature of LL approach showed higher AUC, which agrees with a recent paper ( 26 ). Although we did not find significant difference of AUC between them, the lower 95% confidence interval of AUC at TP1 is 0.51 in the test set, indicating an insufficient diagnosis efficiency.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, further evaluation needs to be carried out in translating such research into clinical practice because most literature in the field had a multi-localization/multi-type tumor cohort design. Deltaradiomics features (Delta-RFs) which capture therapy-induced changes in radiomics features are now being evaluated as a complement to Response Evaluation Criteria in Solid Tumor (RECIST) criteria for monitoring therapeutic response in several tumor types (25)(26)(27)(28)(29)(30)(31). Khorrami et al showed preliminary evidence for clinical use of Delta-radiomics calculated from contrast-enhanced CT images as predictive biomarkers of response to ICIs therapy in NSCLC (31).…”
Section: Introductionmentioning
confidence: 99%
“…Integration of multiple, diverse sources of data using different kind of fusion strategies either at a feature or at a model decision level is a current trend in predictive modeling. In particular, it is very common to add radiomic features to clinical variables that are predictors of the disease outcome in the form of nomograms [36][37][38], which can then be applied and tested within clinical cohorts.…”
Section: Training and Validating The Radiomics Modelmentioning
confidence: 99%
“…Feature Selection 3 (FS3) combines FS1 and FS2 [33,34]. After robust features are selected using test-retest and multiple segmentation, non-redundant features are selected using Pearson's correlation analysis with a threshold of 0.8.…”
Section: Feature Selectionmentioning
confidence: 99%
“…After robust features are selected using test-retest and multiple segmentation, non-redundant features are selected using Pearson's correlation analysis with a threshold of 0.8. FS1, FS2, and FS3 are commonly used as feature selection methods for prognostic studies based on radiomics [9,21,33,34]; therefore, we decided to adopt these feature selection methods in this study. MATLAB R2020a was used for all selection methods.…”
Section: Feature Selectionmentioning
confidence: 99%